DYNAMICS OF EMOTION IN ADOLESCENTS WITH MOTHERS WITH AUTHORITARIAN PARENTING - Azka Amalia Afifi; Dyah Siti Septiningsih (PSIMPHONI, 2021)
This study aims to examine the flow of emotional dynamics in adolescents who have mothers with authoritarian parenting. This is qualitative research. Participants consisted of 3 teenagers, 2 females and 1 male who had a mother with authoritarian parenting. Data were collected by providing authoritarian parenting screening which is then followed by a semistructured interview. The interviews were done using online communication media, such as Whatsapp. The data triangulation techniques were used as the credibility in this study. From the results of the research, it can be concluded that the triggers of emotional dynamics were due to the authoritarian parenting of their mothers, such as the existence of restrictions, punishment and demands. The emotional dynamics experienced by the three participants were their unstable feeling, marked by feelings of anger, fear, boredom, and sadness when they disagreed with their mothers. The outlet of each participant is different. In the process of quelling emotions, each participant prefers to cover up the story or write and end up asleep. Each participant will calm down so that they are not deep far into negative emotions.